A Check List of Exotic Plants in Subankhata Reserve Forest, Baksa District of Assam, India - Choudhury, M.; Sarma, G. C.; Bhattacharya, P.; Boro, A. (Indian Forester, 2016)
Subankhata Reserve Forest is located in between 26 08'97'' to 26 26'17'' N latitude and 91 38'96'' to 91 49'90'' E longitude in Baksa district under Dhansiri Forest Division of the Manas Biosphere Reserve in Assam. A preliminary study was conducted to record the exotic floristic wealth of the Reserve Forest. In the survey, only naturally grown species were undertaken into account. Altogether 63 exotic plant species belongs to 57 genera and 31 families were found in the process.